Essential notes on modeling rental rate for islamic home financing in Indonesia (Journal of Economic Research & Business Administration, 2023)
Homeownership hitherto remains a formidable work in every country. Rental rate that comprises house and rental price is an arduous factor to determine just price to own the home.  This study attempts to unveil some essential notes for Islamic bank in undertaking rental rates for Islamic mortgage financing in Indonesia. By employing the qualitative approach of pedigree on Islamic mortgage financing, this study found some pertinent elements such as the rental price of residential housing, macroeconomics variables, and its heterogeneity and homogeneity factors are among the essential notes to undertake by relevant stakeholders in determining rental rate. The novelty of this study can be considered as the one that initiated to an exploration of rental rates as an alternative element in Islamic home financing in Indonesia. This study implies government policy to consider rental rate mechanism as a new approach to derive just Islamic home financing in Indonesia. In addition, Islamic banks will incorporate this approach as part of their pricing component in determining Islamic home financing. Keywords: Rental Rate, Islamic Home (mortgage)Financing, Macroeconomics, Heterogeneity, Homogeneity.